Media perception of companies’ CSR initiatives : Exemplary case of adidas x Parley for the Oceans - Weber, Kathrin; Pauknerová, Daniela, 1970-; Kašparová, Eva, 1958-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2020)
Corporate social responsibility (CSR) has become one of the most relevant topics in the past years, its relevance peaking in September 2019, with the biggest so-called climate strikes happening worldwide. Rising temperatures and the overall climate change became a global issue, threatening billions of people. It is an undeniable fact that calls for action from individuals, governments, and companies to take over responsibility to prevent this global catastrophe. Furthermore, consumers and the media are challenging the status quo of how most businesses operate and demand fairness. This paper is investigating the changing media perception of a CSR initiative over the course of time, in relation to the salience of the topic of environmentalism. The findings suggest that the media perception of CSR practices is perceived as more positive and genuine due to the company’s collaboration with an environmental organisation. As well as the consultation of field experts gives the initiative the needed professionalism and non-profit cause orientation. All in all, this is associated with a high salience of the topic overall.
Vedoucí práce: Daniela Pauknerová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses